The history of the Kallang River and Kallang Basin : filling in a gap in Singapore’s colonial historiography - Cheang, Tze Mun (Nanyang Technological University, 2020)
This paper examines the history of Kallang River and Kallang Basin from 1819 – 1940 to fill a gap that was not well-researched in Singapore’s colonial history. It argues that the Kallang Basin developed into a regional hub for Southeast Asia and the Kallang River developed into a waterway connecting the inland settlements economic activities with the regional trade at the Basin while becoming a centre of new industries and local infrastructure. The history of the Kallang region reflects government attempts to control the Kallang region’s social space and urban development, and the negotiations between state and nonstate actors as it developed into a regional hub. However, state urban planning rarely goes accordingly and while state institutions gradually became stronger and more influential in the Kallang Basin, nonstate forces in society contested state forces at times and state institutions faced limitations in carrying out their plans. The history of the Kallang River also shows rivers as zones of urbanization located within a broader long-term pattern of urbanization connecting river systems and landscapes. It also demonstrates that rivers were important locales for port-polities, and the creation and transformation of urban centres and landscapes in Southeast Asia and beyond.